Functional neural changes and altered cortical–subcortical connectivity associated with recovery from Internet gaming disorder - Dong, Guang-Heng (J Behav Addict, 2019)
BACKGROUND AND AIMS: Although studies have suggested that individuals with Internet gaming disorder (IGD) may have impairments in cognitive functioning, the nature of the relationship is unclear given that the information is typically derived from cross-sectional studies. METHODS: Individuals with active IGD (n = 154) and those individuals no longer meeting criteria (n = 29) after 1 year were examined longitudinally using functional magnetic resonance imaging during performance of cue-craving tasks. Subjective responses and neural correlates were contrasted at study onset and at 1 year. RESULTS: Subjects’ craving responses to gaming cues decreased significantly at 1 year relative to study onset. Decreased brain responses in the anterior cingulate cortex (ACC) and lentiform nucleus were observed at 1 year relative to onset. Significant positive correlations were observed between changes in brain activities in the lentiform nucleus and changes in self-reported cravings. Dynamic causal modeling analysis showed increased ACC–lentiform connectivity at 1 year relative to study onset. CONCLUSIONS: After recovery from IGD, individuals appear less sensitive to gaming cues. This recovery may involve increased ACC-related control over lentiform-related motivations in the control over cravings. The extent to which cortical control over subcortical motivations may be targeted in treatments for IGD should be examined further.